2008
DOI: 10.1111/j.1365-294x.2008.03956.x
|View full text |Cite
|
Sign up to set email alerts
|

Combining direct and indirect genetic methods to estimate dispersal for informing wildlife disease management decisions

Abstract: Epidemiological models are useful tools for management to predict and control wildlife disease outbreaks. Dispersal behaviours of the vector are critical in determining patterns of disease spread, and key variables in epidemiological models, yet they are difficult to measure. Raccoon rabies is enzootic over the eastern seaboard of North America and management actions to control its spread are costly. Understanding dispersal behaviours of raccoons can contribute to refining management protocols to reduce econom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 87 publications
(178 reference statements)
4
46
2
Order By: Relevance
“…Each local study site was encompassed within a continuous unit composed of the two adjacent game reserves, MGR and KYGR, surrounded by disturbed areas. We quantified site isolation using the following indices: distance from the local study site to the nearest and the farthest borders of the unit, distance from the local site to the edge of the habitat patch where the site is found, distance from the site to the nearest patch of the same habitat as the one where it is found, and sum of the pairwise distances between sites (Cullingham et al 2008). Furthermore, we quantified site area with two indices, namely, size of the habitat patch where the site is found and area of this habitat within the unit.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Each local study site was encompassed within a continuous unit composed of the two adjacent game reserves, MGR and KYGR, surrounded by disturbed areas. We quantified site isolation using the following indices: distance from the local study site to the nearest and the farthest borders of the unit, distance from the local site to the edge of the habitat patch where the site is found, distance from the site to the nearest patch of the same habitat as the one where it is found, and sum of the pairwise distances between sites (Cullingham et al 2008). Furthermore, we quantified site area with two indices, namely, size of the habitat patch where the site is found and area of this habitat within the unit.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Hansson et al 2004). This can be applied in continuous populations and does not require genetic divergence among localities, but does require very thorough sampling (Stow andSunnucks 2004a, 2004b;Cullingham et al 2008;Broquet and Petit 2009). Another approach is to capture the information residing in individuals with immigrant ancestry up to two generations, that is bearing evidence of gene flow.…”
Section: Estimating Dispersalmentioning
confidence: 99%
“…Their study revealed that local populations sorted into two distinct groups, exhibiting either significantly greater or lesser (non-significant) levels of kin-structure than would be expected at random, a pattern primarily driven by the fact that contributions to population persistence stemming from immigration versus natality differed markedly among local populations. This finding, in combination with strong evidence for a high degree of site fidelity of female raccoons to their natal patch (Gehrt and Fritzell 1998, Ratnayeke et al 2002, Cullingham et al 2008, Dharmarajan et a. 2009, Beasley et al 2013, led (Dharmarajan et al 2014) to hypothesize that significant spatial variation in vital rates exists for raccoons inhabiting fragmented agricultural ecosystems, consistent with expectations of a sourcesink population structure.…”
Section: Introductionmentioning
confidence: 77%
“…However, we believe apparent survival of adult female raccoons closely resembles true survival in our study area. Dispersal in raccoons is male-biased (Ratnayeke et al 2002, Cullingham et al 2008, Dharmarajan et al 2009) and predominantly occurs between 0.5 and 1.5 years of age (Gehrt 2003). Moreover, adult females maintain small home ranges within our study area (58 ha) and no permanent emigration was observed among 37 females tracked using radiotelemetry during previous research conducted within our study landscape (maximum home range size was 160 ha; Beasley et al 2007.…”
Section: Population Growth Ratementioning
confidence: 99%